Investigation of electrical, photodiode and photovoltaic properties of Au/ SiO2/n-Si structures with GO and P3C4MT interface - Seymen, Halil; Karata, Sukru (Elsevier Science Sa, 2023)
This study mainly focused on investigating the electrical and photodiode properties of Au/SiO2/n-Si hetero-structures with graphene oxide (GO) and poly(3-cyclohexyl-4-methyl-2,5-thiophene) (P3C4MT) interface. For this, GO and P3C4MT thin layer was grown as an interfacial layer between Au and SiO2/n-Si to create this Au/ (GO:P3C4MT)/SiO2/n-Si hetero structure. From the current-voltage (I-V) measurements, the values of electrical and photodiode parameters such as ideality factors (n), rectification ratios (RR), saturation currents (I0), barrier heights (phi bo), photocurrent (Iph), photosensivity (RR), photoresponse (R), and detectivity (D*) were examined under dark and variable illuminations (from 20 to 100 mW/cm2 by 20 mW/cm2 steps) at room temperature, respectively. Au/(GO:P3C4MT)/SiO2/n-Si heterostructure exhibited a photoconducting behavior under variable illuminations. Furthermore, the photovoltaic properties such as short circuit current (Isc) and open circuit voltage (Voc) were examined under variable illuminations intensities. The experimental results shows that Au/(GO: P3C4MT)/SiO2/n-Si hetero structure under light illumination exhibits a perfect photodiode behavior, and thus this structure can be used as photodiode in optoelectronic devices.
Keywords: Photodiode; Electrical Properties; Photovoltaic; Go And P 3 C 4 Mt Thin Film Layer; Diode; Photodetector; Temperature; Photoresponse